Anemia among women of reproductive age: a cross sectional study in Sub district hospital, Akhnoor - Sharma, Chandan; Badyal, Ashima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Anemia in pregnancy can increase the risk of having a pre-term delivery/babies, which may further lead to low birth weight and sometimes death. Anemia is more prevalent in Asia, with half of the all-anemic women living in Indian subcontinent itself. The objective of the study was to estimate the prevalence of anemia among women in the reproductive age group (15-49) in a rural population set up of Akhnoor. Methods: A population based cross-sectional study was conducted in Sub district hospital, Akhnoor, Jammu, J and K, India, over a period of 6 months from September 2020 to February 2021, on a total of 320 women in the reproductive age group of 15 to 49 years. Results: A total prevalence of 59.06% was found with highest among pregnant females. Out of this total anemic patient 59.78% (113/189) were mild anemic, and 40.22% (76/189) were either moderately anemic or severe. High prevalence of anemia was seen among illiterate women (68.89%). Prevalence was also significantly associated to excessive/ scanty menstruation. Besides, menstrual cycle more than 35 days and less than 21 days were found to be at higher risk of anemia (60.53% and 83.33%). Underweight women were also found at higher risk of anemia (69.52%). Only 88 out of 320 women studied had completed the course of IFA tablets. Conclusions: Several socio-demographic, menstrual, dietary, environmental, and behavioral factors were associated with anemia. Women of reproductive age should be motivated to include food fortification or iron supplementations in their diet.